Production and characterization of monoclonal antibodies with specificity for the S100 beta polypeptide of brain S100 fractions. - Van Eldik, L J (Proc Natl Acad Sci U S A, 1984)
S100 refers to a heterogeneous fraction of low-molecular-weight acidic calcium-binding proteins. We report here production and characterization of two mouse hybridomas that secrete monoclonal antibodies that appear to be specific for the S100 beta polypeptide of brain S100 preparations. By ELISA, RIA, and immunoblotting analysis, the monoclonal antibodies react specifically with S100 beta and show little or no reactivity with any S100 alpha-like polypeptides. In addition, there is no reactivity with the structurally homologous proteins calmodulin and troponin C. The utility of these monoclonal antibodies for immunocytochemical studies of clinical pathology specimens has been demonstrated by examination of S100 beta localization in human autopsy brain and anaplastic astrocytoma sections. S100 beta is localized primarily in glial cell cytoplasm and processes, with no specific staining observed in glial cell nuclei, erythrocytes, or neuronal cells. These monoclonal antibodies may have important applications in pathological examination of surgical specimens as a specific marker for tumors containing S100 beta, will allow a more precise interpretation of the distribution and localization of S100 beta in both normal and neoplastic tissues, and may provide insight into the physiological functions of the S100 proteins. IMAGES: